Relationship between volume of the seminal vesicles and sexual activity in middle‐aged men. (20th May 2016) - Taniguchi, H.; Kawa, G.; Yoshida, K.; Takayasu, K.; Kinoshita, H.; Matsuda, T.
Summary: The relationship between volume of the seminal vesicles and the frequency of sex and sexual function in middle‐aged men is not clear. This study included 81 patients who were diagnosed with localized prostate cancer. Volume of the seminal vesicles was examined using a volume analyser from computed tomography. Sexual function was subjectively evaluated using the Expanded Prostate Cancer Index Composite and Erection Hardness Score. The frequency of sex was surveyed using our original questionnaire. The mean ± SD age of the patients was 67.7 ± 5.3 years. There was no relationship between the volume of seminal vesicles and age of the patients. Volume of the seminal vesicles in patients who answered that they had sexual activity at least once a year was significantly larger than in those who answered no sexual activity for several years ( P  < .01) Moreover, among sexually active, middle‐aged men, volume of the seminal vesicles was significantly larger in those who had a sexual frequency once every 3 months than in those who had a sexual frequency once every 6 months or once a year ( P  < .05). Our study suggests that the volume of seminal vesicles of middle‐aged men is correlated with sexual activity.